Investigating the contributions of active, playful learning to student interest and educational outcomes - Elias Blinkoff; Kimberly T. Nesbitt; Roberta Michnick Golinkoff; Kathy Hirsh-Pasek (Acta Psychologica, 2023)
A growing body of evidence from the science of learning demonstrates the educational effectiveness of active, playful learning. Connections are emerging between this pedagogy and the broad set of skills that it promotes in learners, but potential mechanisms behind these relations remain unexplored. This paper offers a commentary based on the science of learning and interest development literature, suggesting that interest may mediate the relation between active, playful learning and student outcomes. This theory is established by identifying principles of active, playful learning that predict interest development and associations between learner interest and key skills for success in the classroom and beyond. Future research should investigate the dynamic relation between active, playful learning, interest, and student achievement over time and across phases of interest while taking a broader set of student outcomes into account.